Penelitian Pemetaan Permodalan UMKM Dusun Cupak Desa Cupak Kecamatan Ngusikan Kabupaten Jombang - Maulidah Narastri; Andhika Mahendra; Adam Permana Putra; Elisa Ayu Febryanti; Chyntia Dewi Nur Oktavian; Qhuluqi Alya; Nur Aini Qurrata A’yun; Cindy Larissa (Universitas Muhammadiyah Manado, 2023)
Capital is a very important component in the development of MSMEs. In Cupak village itself, capital mapping is still underdeveloped, the problems faced by MSMEs in Cupak village are very many, especially marketing problems, lack of business capital, and locations that are far from the outreach of other communities. this research usesquantitative method with linear regression analysis because this method consists of one variable. With calculations using SPSS as a tool to calculate the data that has been obtained. With this research it is hoped that it will be useful for MSMEs in Cupak village and can be used as reference material for MSMEs to analyze, implement marketing activities in their businesses, as data assistance for the development of MSMEs and as an evaluation of MSMEs